2016
DOI: 10.1590/1982-0224-20140127
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Poecilia sphenops Valenciennes, 1846 (Cyprinidontiformes: Poeciliidae) at the Emiliano Zapata Reservoir in Morelos, Mexico

Abstract: Poecilia sphenops is a native species recently recorded in the Balsas basin and the Amacuzac River in Morelos (Mexico), in which it is abundant and widely distributed. This study analyzed some aspects of the reproductive biology of Poecilia sphenops from the Emiliano Zapata Reservoir, in Central Mexico. Specimens were collected using a 20 m-long seine with a 5 mm mesh size, from January to December 2006. A total of 581 specimens were collected: 407 females (70.0%), 83 males (14.3%) and 91 individuals with no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
3
5
0
Order By: Relevance
“…Gómez-Márquez et al (1999) reported SL at first maturity of 22 mm in male of H. bimaculata and 27 mm in females. In this study, P. sphenops showed reproductive efficiency proportional to size, in agreement with several authors (Gómez-Márquez et al, 2016;Trujillo-Jiménez & Toledo, 2007). Sexual maturity is a function of size, and may be influenced by age, as well as abundance and availability of food, water temperature and day length (Nikolsky, 1978).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Gómez-Márquez et al (1999) reported SL at first maturity of 22 mm in male of H. bimaculata and 27 mm in females. In this study, P. sphenops showed reproductive efficiency proportional to size, in agreement with several authors (Gómez-Márquez et al, 2016;Trujillo-Jiménez & Toledo, 2007). Sexual maturity is a function of size, and may be influenced by age, as well as abundance and availability of food, water temperature and day length (Nikolsky, 1978).…”
Section: Discussionsupporting
confidence: 92%
“…A higher proportion of females favors reproductive success, spread, and successful invasion. The GSI values indicated that P. sphenops and P. bimaculatus are iteroparous, which permits population increase and indicates effective exploitation of environmental resources, which is similar to those reported byGómez-Márquez et al (2016).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The males of P. mexicana showed negative growth, except in the sub-optimal condition, which suggests that body parts do not grow at a similar rate, and thus fish grow in length more than in weight. Similar results have been found in other species, such as Poecilia sphenops (Martínez-Trujillo, 1983;Gómez-Márquez et al, 2016;Ramírez-García et al, 2018), P. gracilis (Contreras-MacBeath & Ramírez-Espinoza, 1996;Gómez-Márquez et al, 2008), and Pseudoxhiphorus bimaculatus (Ramírez-García et al, 2018). However, Contreras-MacBeath & Ramírez-Espinoza (1996) reported isometric growth for P. gracilis.…”
Section: Discussionsupporting
confidence: 86%